Sosialiasi dan Pelatihan Pengolahan Sampah di Kecamatan Pagerbarang Kabupaten Tegal - Zulfaidah Ariany (Jurnal Pengabdian Vokasi, 2020)
Garbage is often considered trivial by the community so that it causes negative impacts if left scattered or piled up. Can have a positive impact or make money if it is utilized to the full. The type of waste that is often produced by most people is household organic waste that is easy to rot and decompose. One way that can be done to reduce household organic waste is to innovate a versatile organic waste processing tool such as composter. This tool converts organic waste into organic fertilizer. With the processing of organic waste can reduce air pollution, and also produce fertilizer at a lower cost. Useful for fertilizing the soil. Therefore, training and assistance in the processing of organic waste using composter equipment was carried out, as was done in desa Semboja with the LIBAS program. Training and assistance in making eco-bricks in several villages such as in desa Surokidul and desa Pagerbarang. Introduction to the concept of the Garbage Bank, its management and development, training in making handicrafts made of plastic, the use of plastic waste into pot-verticulture media, and processing plastic waste obtained by waste banks into oil. Many things can be done to empower village communities so that they are more independent, live healthier and happier.